Pengaruh Motivasi, Pengalaman Kerja dan Kompetensi terhadap Kinerja Melalui Kepuasan Kerja Pegawai Pemerintah Provinsi Kepulauan Riau - Syamsul, Sari Baiti; Wibisono, Chablullah; Ngaliman, Ngaliman (Universitas Batanghari Jambi, 2025)
The aim of this research is to analyze motivation, work experience, competence, and performance of Riau Islands Provincial Government employees. The target population in this research is the functional position of Civil Servants in Agencies in the Riau Islands Province. The sample size is adjusted to the analysis model used, namely the Structural Equation Model (SEM). The results of this research found that the job satisfaction variable can have a positive and significant influence on the variables of work motivation, work experience and competence on the performance of Riau Islands Provincial Government employees.